PERANAN LEMBAGA BANTUAN HUKUM DALAM MEMBERIKAN BANTUAN HUKUM KEPADA MASYARAKAT TIDAK MAMPU DITINJAU DARI PUTUSAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2014 - La Ode Sarman; Nasrin Nasrin (Jurnal Ilmu Hukum Kanturuna Wolio, 2022)
Indonesia is a state of law. This is in line with the provisions of Article 1 paragraph (3) of the 1945 Constitution of the Unitary State of the Republic of Indonesia which reads that the State of Indonesia is a state of law. Then in article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, it reads "all citizens have the same position in law and government and are obliged to uphold the law and government without exception". Likewise, it is also explained in Article 28D paragraph (1) of the 1945 Constitution which reads that every citizen has the right to recognition, guarantee, protection and fair legal certainty and equal treatment before the law. Therefore, the constitution guarantees that every citizen who stumbles upon a legal case has the right to obtain guarantees and legal assistance from the state. The problems in this study are (1) What is the role of LBH in providing legal aid to underprivileged communities? (2) What is the role of legal aid institutions (LBH) in providing legal assistance to underprivileged communities in accordance with the decision of the Supreme Court (MA) number 1 of 2014?. The objectives of this research are: (1) Knowing how the role of legal aid institutions (LBH) in providing legal aid to underprivileged communities is? (2) Knowing what is the role of legal aid institutions (LBH) in providing legal assistance to underprivileged communities with the decision of the Supreme Court (MA) Number 1 of 2014?. The research location is at POSBAKUMADIN Baubau City. Based on the formulation of the problem, objectives, benefits and research methods used, the authors conclude that the role of LBH in this case POSBAKUMADIN Baubau City has not been effectively implemented for the people of Baubau City, this is due to the lack of public knowledge about free legal aid and the absence of assistance from the public. Baubau city government in this case the special APBD budgeting for free legal aid for the poor.